Management of Infectious Mononucleosis in Paediatric Athletes - Tłustochowicz, Katarzyna; Kowalik, Adrianna; Krajewska, Agnieszka; Korba, Magdalena; Polkowska, Wiktoria; Malicka, Natalia; Korzeniewska, Agnieszka Maria; Dębczak, Julia Agnieszka; Łuczak, Karolina (Quality in Sport, 2026)
Background. Infectious mononucleosis (IM), most commonly caused by the Epstein–Barr virus (EBV), affects primarily adolescents and young adults between 15 and 24 years of age, populations with high rates of sports participation. Although IM is usually self-limited, ,its symptoms most often include fever, pharyngitis, posterior cervical lymphadenopathy, fatigue, and malaise. Aim of study. This review aims to summarize the current evidence on the diagnosis, clinical management, and return to play (RTP) recommendations for athletes and paediatric athletes with IM. Materials and Methods. The review was based on a search of articles published in the PubMed database. Search terms included: infectious mononucleosis, Epstein-Barr virus, splenic rupture, splenomegaly, return to play and Monospot test Current state of knowledge. Prolonged fatigue and the risk of splenic rupture may significantly disrupt training and competition. The most relevant sports-related complication is splenic rupture, which is associated with splenomegaly and occurs most often early in the disease course. Conclusions. RTP decisions should be individualized based on symptom resolution, clinical findings, the type of sport (contact vs non-contact), and shared decision-making. The general consensus is to avoid contact sports and strenuous training for at least 3–4 weeks. Ultrasound may be helpful in selected cases, but its routine use is limited by the wide variability in baseline spleen size and the absence of validated thresholds for safe RTP.